EFFECTIVENESS OF BRONCHODILATOR AND CORTICOSTEROID TREATMENT IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) - Veryanti, Putu Rika; Wulandari, Ainun (Journal Pharmaceutical Science and Application; Vol 2 No 1 (2020): Journal Pharmaceutical Science and Application, 2020)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic airway disease which is characterized by progressive airway obstruction. Bronchodilators and corticosteroids are the first choices of therapy in COPD patients. The goal therapy of COPD patients is to prevent respiratory failure, which can impact on death. But nowadays, the mortality rate due to COPD continues to increase. WHO predicts mortality from COPD in the year 2030 will be ranked third in the world. This high mortality can be caused by the ineffectiveness of therapy given. Objective: The aim of this study is to find out the effectiveness of bronchodilator and corticosteroid treatments in COPD patients. Methods: An observational study conducted retrospectively in the 2018 period at Fatmawati Central General Hospital. The effectiveness of therapy was assessed from the patient's clinical condition, blood gas values (PaO 2 & PaCO 2 ) and the average length of stay (AvLOS). Results: COPD was mostly suffered by males (83,33%), and the highest age for COPD was in the range of 45 years and above (90%). Bronchodilator that commonly prescribed were albuterol (30.08%), ipratropium bromide (12.2%), fenoterol hydrobromide (10.57%), terbutaline sulfate (8.13%), theophylline (1.63%) and aminophylline (5.69%), while the corticosteroids were budesonide (17.07%), methylprednisolone (9.76%) and dexamethasone (4.88%). Bronchodilator and corticosteroid had improved patient's clinical condition (96.67% patients) and also improved PaO 2 & PaCO 2 values patients. There was a significant improvement in PaO2 and PaCO2 value in COPD patients (p <0.05). Conclusion: Bronchodilator and corticosteroid in COPD patients had improved patient's clinical condition and PaO 2 & PaCO 2 values, but the average length of stay exceeds the standard (6-9 days). Keywords: Bronchodilator, Corticosteroid, COPD, Blood Gas Analysis, Average Length of Stay